Transformation of Rahn's Thought Development as Sharia Capital Business - Suherli, Ian Rakhmawan (Iqtishodia: Jurnal Ekonomi Syariah, 2024)
This research writes about the transformation of the development of rahn (sharia pawn) thinking as a sharia capital business. Rahn or sharia pawn was originally seen as a tabarru' (social) contract to help, but developed into a tijarah (commercial) contract that had economic benefits. The writing explains the legal basis of rahn from the Quran, Hadith, fiqh rules, to the laws and fatwas of DSN MUI. The development of rahn thought is discussed from the time of Prophet Muhammad SAW, Khulafaur Rashidin, Abbasid, to contemporary times. It also explained the terms of pawn goods (marhun), the types of contracts in rahn, and the potential of rahn as an instrument of sharia financing today. In conclusion, rahn thought has undergone a transformation from tabarru' to tijarah. Rahn has the potential to become a profitable sharia capital business that is free from usury, in addition to the potential for new types of intangible goods as valuable and valuable goods that can be used as al marhuun (collateral).